Developmental-Behavioral Pediatricians' Diagnosis and Coding of Overweight and Obesity in Children with Autism Spectrum Disorder. Issue 4 (May 2020) - Walls, Morgan; Curtin, Carol; Phillips, Sarah; Eliasziw, Misha; Jackel, Carissa; Must, Aviva; Bandini, Linda; Broder-Fingert, Sarabeth
ABSTRACT: Objective: The prevalence of obesity in autism spectrum disorder (ASD) is high, and managing obesity in children with ASD can be challenging. The study's objective was to examine developmental-behavioral pediatricians' (DBPs) coding practices for overweight/obesity in children with ASD and patient characteristics associated with coding. Methods: We analyzed the clinical data on children with ASD with at least 1 visit at one of 3 developmental-behavioral pediatrics network sites between January 2010 and December 2011. Weight status was calculated using body mass index z-scores. For children meeting the criteria for overweight/obesity, we assessed the frequency of weight-related ICD-9 diagnosis codes at DBP visits, used multivariable logistic regression to determine characteristics associated with the presence of these codes, and examined the prevalence of weight-related codes relative to other diagnosis codes. Results: The sample included 4542 children, ages 2 to 19 years. 15.5% of children met the criteria for overweight, 14.7% for obesity, and 6.3% for severe obesity. Of children meeting the criteria for overweight/obesity/severe obesity, 7.5% had a weight-related code documented at their visits. Children with obesity or severe obesity and older children had higher odds of having a weight-related code. Compared with not being on medications, atypical antipsychotics use was significantly associated with increased odds of having a weight-related code. Of 3802 unique ICD-9 diagnosis codes documented at any visit during the study period, only 4% were related to weight. Conclusion: Few children meeting the criteria for overweight/obesity had documented weight-related codes. Weight-related coding was more likely for children with obesity, who were older, and those taking atypical antipsychotics.